Framtagande av lokala utvecklingsplaner i samhällsplaneringen : Ur ett organisatoriskt perspektiv - Eriksson, Annika (2015)
In previous studies it has been shown that the structure of our society is divided into sectors. This is one of the reasons why it is difficult to cooperate across sector borders, which are barriers to sustainable urban development. Local authorities are working to find ways for more comprehensive management from a holistic perspective, but the progress is slow.The aim of the thesis is to illustrate how complex planning can be organized to meet the development goals at the neighborhood level. In a particular case, a comparison between two different working methods was made, a project work compared to a process-oriented approach. The goal was to make an analysis in terms of resource use and quality that can be the basis for selection of future work. The study was limited to follow the work of preparation of the development plan in Råneå, which is a part of the municipality of Luleå in northern Sweden. The quality modes analyzed against are those from the directives and the expectations of the development, which can be found detailed in the municipal policy documents and master plan. The goals and intentions of the municipal planning for sustainable development has been in focus because they form the basis of the compered quality modes. The study was based on a detailed description and analysis of the two approaches (project- or process-oriented) on the basis of a contract to develop a development plan on the neighborhood level. The comparison was based on the objectives and intentions in the municipal policy documents and master plan.One of the conclusions is that the choice of approach (project- or process-oriented) is important for quality and effectiveness, but the importance and significance depends on a number of other factors. For example, the purpose and goals of the development, timetable, financial condition, stakeholders, customers etc. Both options are good in themselves, but depending on what to use them for, select the method that is most suited for the task. Validerat; 20150622 ...